Factors that hinder artificial insemination in sheep and its impact on fertility, pregnancy and parturition rates: : systematic literature review - Cáceres Bautista, Daniela; Mogollón W, Edgar Mauricio (Spei Domus, 2020)
Introduction: The increasing importance of sheep farming in Colombia, its national inventory, the production in tons of meat/year and the increase in per capita consumption, demand interventions to improve the reproductive indicators of the species, with support among others of the use of reproductive biotechnologies. For this reason, it is pertinent to identify the factors that hinder Artificial Insemination (AI) in sheep, in order to intervene on them and contribute to the improvement of their reproductive indicators and the welfare of the producers.Methodology: A systematic literature review was conducted to identify the main factors reported, which make pregnancy difficult through artificial insemination in sheep. For the selection of articles, its open access nature was taken into account, and research products related to morphometric parameters, AI techniques that cross the cervix (IAV, IAC, IATC) and laparoscopic AI, forms of conservation were consulted of semen (fresh, refrigerated and frozen-thawed) and estrus synchronization protocols, which include fertility, pregnancy or delivery rates within their results. We excluded articles written in languages ​​other than Spanish, Portuguese and English, species other than sheep, as well as results that did not incorporate synchronization protocols, the presentation of semen, and the type of AI technique used, fertility rates, pregnancy or lambing.Results: Forty-four articles were selected, which met the inclusion criteria, of which 15 were related to morphometric parameters, forms of the cervical os and its correlation with age, and 29 were related to AI techniques, the type of semen conservation, synchronization protocols and their correlation with fertility, pregnancy and lambing rates.Conclusions: This work made it possible to clarify that the main factors that hinder AI pregnancy in sheep are the age of the animals, the morphometric parameters of the cervix, the type of AI technique and the presentation of the semen.
Keywords: Artificial insemination; transcervical insemination; morphometric parameters; IA techniques; sheep